The Effect of Treated Overt Hypothyroidism on Outcomes in Twin Pregnancies - Rosner, Jonathan Y.; Fox, Nathan S.; Saltzman, Daniel; Rebarber, Andrei; Gupta, Simi (American Journal of Perinatology, 2017)
Objective The objective of this study was to determine if treatment of overt hypothyroidism in twin pregnancies reduces adverse outcomes associated with overt hypothyroidism in pregnancy.Methods This is a retrospective cohort study of all patients who were presented with twin gestations between 2005 and 2013 to a single obstetrical practice. Patients who were diagnosed with overt hypothyroidism were identified. Patients were followed up with serial thyroid function tests and treated appropriately. Rates of adverse pregnancy outcomes were compared between patients with and without hypothyroidism with p < 0.05 used for significance.Results In this study, 612 twin pregnancies were included; 85 patients were diagnosed with overt hypothyroidism. Patients with overt hypothyroidism were more likely to have had in vitro fertilization (78 vs. 62%; p < 0.01). After adjusting for confounding variables, patients with overt hypothyroidism had no increased risk of spontaneous preterm birth < 37 weeks' gestation (adjusted odds ratio [aOR]: 0.833; 95% confidence interval [CI]: 0.498–1.393), intrauterine growth restriction (aOR: 0.720; 95% CI: 0.446–1.163), gestational diabetes (aOR: 0.812; 95% CI: 0.353–1.871), or composite adverse outcomes (aOR: 0.659; 95% CI 0.391–1.111) compared with patients who did not have overt hypothyroidism. There was a trend toward decreased hypertensive disorders of pregnancy (aOR: 0.470; 95% CI: 0.234–0.944).Conclusion Our study shows that in twin gestations, there is no increased risk of adverse pregnancy outcomes between patients with treated overt hypothyroidism and those without overt hypothyroidism.
Keywords: twins; hypothyroidism; adverse outcomes; levothyroxine